The Influence of Organizational Culture and Working Environment on Employee Performance at PT. Pusaka Ayu Bahari - Prayoga Langgeng Basuki; Zulvia Khalid (Penerbit Goodwood, 2021)
Purpose: This research was conducted to determine the relationship between organizational culture and working environment on Employee Performance. Research Methodology: Data analysis utilized in this study consists of; data quality test, classical assumption test, multiple regression analysis and hypothesis testing. The number of participants in this study was 52 (employee) at PT. Pusaka Ayu Bahari (South Jakarta) uses the Incidental method and should experience working in the company. Results: The results of this study indicate that there is a significant positive partial influence of the relationship between the two independent variables, namely Organizational Culture and Working Environment on Employee Performance, result details from this study are seen as follows: that Organizational Culture has an influence towards Employee Performance. and Working Environment has an influence towards Employee Performance.